Physicochemical and thermodynamic properties of binary and ternary liquid mixtures / Arshid Nabi - Arshid , Nabi (2019)
In this study, the experimental viscosity  , density  , ultrasonic velocity, u and refractive index D n for the binary liquid mixtures were measured. The viscosity  for pure N,N-dimethylformamide (DMF) and acetone (ACT) over the whole composition range of their binary mixtures were measured between 298.15 and 313.15 K. The density  and ultrasonic velocity u of pure dichloromethane (DCM) solvent with its binary mixtures of pure solute components methanol (Me-OH), ethanol (Et-OH), propan-1-ol (Pr-OH) and butan-1-ol (Bu-OH) were measured at (298.15, 303.15 and 308.15) K. In addition the experimental densities (  ), ultrasonic speeds (u), the refractive indices ( D n ) of binary mixtures of dichloromethane (DCM) with acetone (ACT) and dimethylsulfoxide (DMSO) were measured over the whole composition range at temperatures 298.15, 303.15 and 308.15 K. The deviations in viscosity  , Gibbs free energy of activation G, entropy * S , enthalpies H , excess molar volume E m V , deviation in isentropic compressibility s k , deviation in specific acoustic impedance Z , deviation in intermolecular free length f L and deviation in ultrasonic velocity u were calculated. Moreover, beside the above experimentally obtained deviations from defined expressions involving only measurable quantities, the theoretically derived deviations in refractive indices D n and theoretical compressibilities s k values from Benson–Kiyohara theory were applied to the binary mixtures (DCM + DMSO/ACT). The conductor-like screening model COSMO-RS σ-profile which refers to the chosen systems of the pure molecular components, was calculated. The experimental results were found to be in a good agreement with some of the theoretical predictions. The study was extended to ternary liquid mixtures focusing on drug and surfactant interactions. Volumetric, conductometric, tensiometric and spectroscopic methods were utilized for the (a) cetyl trimethylammonium bromide (CTAB) in aqueous paracetamol and (b) sodium dodecyl sulfate (SDS) with dopamine (DA) in ethanol (Et-OH) ternary mixtures. The critical micelle concentration (CMC) values have been determined by different experimental methods that yielded identical CMC values. The measured data were used to calculate various useful thermodynamic parameters, which can completely characterize any mixture. The standard micellar (mic) free energy , enthalpy and entropy were calculated from the temperature dependence of the equilibrium constants of micelle formation using the pseudo- phase separation model. In addition Fourier transform infrared analysis (FTIR) was carried out to estimate the possible interactions prevailing for CTAB in aqueous paracetamol the micellar systems. The experimental density data was utilized to estimate the apparent molar volumes at infinite dilution apparent molar volumes at the critical micelle concentration and apparent molar volumes upon micellization at different temperatures. The interfacial parameters such as the surface excess concentration standard Gibbs free energy of adsorption at interface and the minimum surface area per molecule were calculated. The results were discussed in the light of various interactions prevailing in the mixed systems under the applied physical conditions. The overall study, which is an interplay of experiment and theory, seems to suggest that the crucial relevance of both factors must be simultaneously considered to develop a coherent understanding. 0mic G 0mic H 0mic S o V cmc V m V  max  ad G min A